2005
DOI: 10.1620/tjem.207.109
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Bronchospastic Factors in Asthma Exacerbations Caused by Upper Respiratory Tract Infections

Abstract: It is still uncertain how viral respiratory infections cause acute exacerbations of bronchial asthma, although several mechanisms have been proposed. We studied the relationship between the airway narrowing and the inflammatory and bronchospastic factors in peripheral venous blood and urine, in 30 patients with asthma at the exacerbations caused by upper respiratory tract infections (URTIs). Acute exacerbations caused decreases in peak expiratory flow rate (PEFR) in all 30 patients with asthma. Asthma exacerba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Although previous reports showed serum ECP [7,8,9,10] and serum or plasma cytokine/chemokine production [7,10,11,12,13,14,15,16,17,18,19] in acute exacerbations of asthma, this is the first report to show the profiles of ECP and 27 cytokines/chemokines in serum samples of patients with acute and stable asthma, and in controls. In this study, serum ECP was significantly elevated in acute asthma compared with stable asthma and controls.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although previous reports showed serum ECP [7,8,9,10] and serum or plasma cytokine/chemokine production [7,10,11,12,13,14,15,16,17,18,19] in acute exacerbations of asthma, this is the first report to show the profiles of ECP and 27 cytokines/chemokines in serum samples of patients with acute and stable asthma, and in controls. In this study, serum ECP was significantly elevated in acute asthma compared with stable asthma and controls.…”
Section: Discussionmentioning
confidence: 54%
“…However, evidence suggests that treatment with inhaled corticosteroids does not improve airway inflammation induced by rhinovirus infection [23]. On the other hand, oral glucocorticoids improve lung function and decrease serum IL-6, soluble ICAM-1 and ECP levels [10]. In this study, treatment comprising systemic corticosteroids resulted in decreases in serum levels of ECP, IL-5, IL-6, IL-1ra and IP-10, but not IL-8, IL-10, G-CSF and MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment with inhaled corticosteroids does not improve airway inflammation induced by rhinovirus infection [30]. On the other hand, oral glucocorticoids improve lung function and decrease the elevation of serum IL-6, soluble ICAM-1, and ECP [31]. Recently, we reported that treatment that included systemic corticosteroids could decrease serum levels of ECP, IL-5, IL-6, IL-1ra, and IP-10 in acute exacerbation of childhood asthma [32].…”
Section: Discussionmentioning
confidence: 99%
“…As we know, almost all patients with early asthma categorized into mild asthma, and some of these patients increase their severity over time. For instance, upper respiratory tract infections cause acute exacerbations of asthma (Yasuda et al 2005).…”
Section: Therapy For Airway Remodeling In Asthmamentioning
confidence: 99%